PERSEPSI KONSUMEN TERHADAP PENERAPAN KECERDASAN ARTIFISIAL PADA DIGITAL MARKETING: STUDI KASUS PADA APLIKASI E-COMMERCE TIKTOK - Susanto, Dannield Claixiuss; Wahyono, Teguh (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze consumer perceptions of the implementation of Artificial Intelligence (AI) in digital marketing on the TikTok Shop e-commerce application. The research employed a quantitative approach using a survey method involving 100 respondents who had used AI-based features such as chatbots, product recommendations, and personalized advertisements. Data were collected through Likert-scale questionnaires and analyzed using IBM SPSS through validity, reliability, and simple linear regression tests. The results indicate that the implementation of AI has a positive and significant effect on consumer perceptions. Consumers perceive AI features as capable of improving convenience, comfort, and the effectiveness of digital shopping experiences through more relevant product recommendations and responsive services. However, aspects related to trust and personal data security remain major concerns for some users in utilizing AI technology on e-commerce platforms. This study demonstrates that AI implementation plays an important role in shaping consumer experiences and perceptions toward digital services. Therefore, e-commerce companies are expected to enhance system transparency and data security in order to maintain consumer trust in the digital business environment.